Resolution for Governor's Advisory Committee on Mental Health (1960)
This 7 page document is a resolution for the governor's advisory committee on mental health in regards to salary adjustments for all mental professionals/personnel. This document was written on September 22, 1960 om which the governor's advisory committee on Mental Health has engaged in a comprehensive review of California's mental health program encouraging progress is being made toward those objectives which must ultimately be achieved. A recommendation of this committee that the salaries for medical, clinical psychology, and psychiatric social work and nursing service classes will be raised for all employees. In page 2, a diagram of the recommended salaries for mental hygiene treatment personnel and estimated cost is given, exhibiting the proposed salary range and the estimated cost.